2008
DOI: 10.1179/136485908x337607
|View full text |Cite
|
Sign up to set email alerts
|

A parasitological survey, in rural Zanzibar, of pre-school children and their mothers for urinary schistosomiasis, soil-transmitted helminthiases and malaria, with observations on the prevalence of anaemia

Abstract: 'Kick-out-Kichocho' is an integrated helminth-control initiative that is aimed at reducing the burden of urinary schistosomiasis and soil-transmitted helminthiases (STH) on Zanzibar Island (Unguja), in Tanzania. Like other initiatives based on preventive chemotherapy, the programme is mainly school-based and, consequently, pre-school children (aged < or =6 years) are not targeted specifically. To assess the importance of urinary schistosomiasis, STH and malaria, as well as the occurrence of anaemia and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…18 Previous studies have highlighted such early Schistosoma infection in areas of high endemicity. 25,28,33,34 The negative health impact of such early infections has been emphasized. 31,32,35,36 Our observation of CCA detected in the urine of a child as young as 3 months in the absence of S. mansoni eggs in fecal samples is in line with recent observations from a study in Uganda using different approaches for detecting Schistosoma infections in pre-school-aged children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Previous studies have highlighted such early Schistosoma infection in areas of high endemicity. 25,28,33,34 The negative health impact of such early infections has been emphasized. 31,32,35,36 Our observation of CCA detected in the urine of a child as young as 3 months in the absence of S. mansoni eggs in fecal samples is in line with recent observations from a study in Uganda using different approaches for detecting Schistosoma infections in pre-school-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]28,29 It has also been discussed whether preventive chemotherapy should be extended from schoolaged to pre-school-aged children. 27,[30][31][32] However, there are a number of issues that must be addressed before policy recommendations can be made regarding the inclusion of preschoolers in preventive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the prevalence of S. haematobium infection has fallen to below 10%. However, transmission hotspots remain (Stothard et al, 2009;Knopp et al, 2013a, b), and visible haematuria, microhaematuria and urinary tract pathology associated with urogenital schistosomiasis are still common (Savioli et al, 1990;Sousa-Figueiredo et al, 2008;Stothard et al, 2009). Successes in the reduction of infection prevalence and intensity have been mainly attributed to the regular administration of preventive chemotherapy on the islands, but a considerable improvement in socioeconomic living standards, including access to safe water and household latrines, also need to be considered (Stothard et al, 2009;Guidi et al, 2010;Knopp et al, 2013b).…”
Section: Schistosomiasis In Zanzibarmentioning
confidence: 99%
“…Other researchers have also demonstrated that young children in several African countries (including Nigeria, Cote d'Ivoire, Kenya, Mali, Uganda, and Zimbabwe) are infected with schistosomes. 2,17,[30][31][32][33] In addition, in some areas, their infection levels are as high as those in their caregivers; these caregivers, however, were eligible for treatment, while the infected children remain untreated for several years (as reviewed by Stothard et al 28 ). Furthermore, the limited investigations describing and quantifying morbidity in this age group have shown that these infections in young children are clinically significant.…”
Section: Challenging the Barriers To Treatmentmentioning
confidence: 99%